Fabrication and in vitro biological activity of βTCP-Chitosan-Fucoidan composite for bone tissue engineering - Puvaneswary, S.; Talebian, S.; Raghavendran, H.B.; Murali, M.R.; Mehrali, M.; Afifi, A.M.; Abu Kasim, N.H.; Kamarul, Tunku (Elsevier, 2015)
We developed tricalcium phosphate-chitosan-fucoidan biocomposite scaffold (TCP-Ch-Fu) by using the freeze-drying technique. The fabricated biocomposite scaffolds were analyzed by spectroscopy and porosity measurement. The biomechanical properties of scaffolds were assessed by compression test and the results suggested that the incorporation of Fucoidan into the biocomposite improves the compression strength of scaffolds. Biomineralization of scaffolds was evaluated by soaking them in simulated body fluid and the results revealed that the addition of Fucoidan into the scaffolds enhanced the formation of apatite layer on the surface of biocomposite after 7 days of immersion. Alamar Blue assay confirmed that the cell viability of human-derived bone marrow stromal cell was superior in the TCP-Ch-Fuscaffold. The addition of Fucoidan to TCP-Ch increased the release of osteocalcin, confirming that it can support osteogenic differentiation of human mesenchymal stromal cells in in vitro culture. Thus, TCP-Ch-Fu could be a potential candidate for bone-tissue engineering applications. (C) 2015 Elsevier Ltd. All rights reserved.